Analysis of the end-to-end encryption algorithm NTRU PRIME IIT UKRAINE taking into account known attacks - Gorbenko, I.D.; Kachko, O.G.; Yesina, M.V. (Radiotekhnika, 2017)
Modern cryptographic transformations of the end-to-end encryption type, namely – NTRU-like cryptosystems are considered. A new cryptographic system NTRU PRIME IIT UKRAINE was created based on existing cryptographic transformations of this type. A brief description of this cryptosystem is presented and an analysis of its resistance to known attacks is carried out, conclusions are made and recommendations are given.